Between memory and history: the restoration of Tulbagh as cultural signifier - Augustyn-Clark, Jayson (School of Architecture, Planning and Geomatics, 2017)
This dissertation examines heritage as a social construct by way of critically accessing the precursors, proponents and processes of the Tulbagh restoration. This research is focused on understanding the reasons why and how, after the earthquake of 1969, Church Street was reinstated to its 'historic' 18/19th century appearance. This reconstructive restoration is unpacked within its South African socio-political, 20th-century situation to examine the motivations of the proponents behind the restoration as well as their conservation philosophies that underpinned the stylistic reconstruction of Tulbagh back to what was regarded as its Cape Dutch 'best'. The study comprises of an examination of both the theoretical development and practical application of reconstructions. Research traces the development of conservation in South Africa, first under the Union government and then under the Afrikaner Nationalist government to understand how Afrikaner Nationalism was superseded by the creation of a white South African identity. Pierre Nora's theories around memory and identity are explored and applied in order to contextualise the Tulbagh case study in a theoretical framework to highlight similarities and differences. The proponents of the Tulbagh restoration consisted of a wide and varied selection of the South African conservation fraternity and included the National Society, the Cape Institute of Architects, historian Dr Mary Cook, the Simon van der Stel Foundation, Anton Rupert and his Historic Homes Company, Gawie and Gwen Fagan and Dr Hans Fransen, as well as the National Monuments Commission/Council. These same role players came together in the decade before the earthquake to formalise their association, conservation resolve and philosophies. The findings of the study suggest that although united with a common vision, philosophy and determination, these conservation advocates all had their own agenda and differing motivations for their involvement in Tulbagh's restoration. Motivations ranged from straightforward conservation concern and a response to the threat of cultural devastation on one hand to ideological nation-building ideals and Afrikaner nationalism on the other. Although politics impacted early on and all three levels of government funded the bulk of the restoration costs, the diversity of the proponents suggests that this project was more complex than being motivated primarily by nationalism.